Simulation of in-vehicle network CAN (in)security - Rosdee, Nur Fadhilah Ajwa; Ali Azmi, Nur Nadiah; Mansor, Hafizah (IIUM Press, 2022)
In-vehicle network security is becoming one of the leading research fields in the cybersecurity area. Modern automobiles consist of Electronic Control Units (ECUs), microcontrollers that control the operations of a vehicle. These ECUs are mainly interconnected through an in-vehicle Controller Area Network (CAN), a message-based protocol that allows communication between different ECUs. The vulnerabilities of CAN which have no encryptions, authentication and integrity checking attributes are widely known but continuous research is made on the security and exploitation of CAN. This is because, the safety and security of vehicles and passengers have become more concerning due to the increase of external and internal vehicle communications. Our paper aims to discuss related works of CAN bus vulnerabilities and security through literature review. This paper conducts simple cyberattacks against CAN bus by data collection, data analysis and attack experiment on the Instrument Cluster Simulator (ICSim) with the help of CAN network analysis tool, CANalyse. CAN packets were collected and analysed and the ID for a number of car functions in ICSim were determined. Attack experiments resulted in sniffing and replay attacks against CAN buses were valid. Finally, from these findings, the paper proposes recommended security measures of CAN bus which are network segmentation, cryptography-based method, and Intrusion Detection System (IDS).